Murdock, Kingman County - Smith, Austin (Kansas State University, The Chapman Center for Rural Studies, 2012)
Murdock, Kansas, started out as New Murdock in 1884 and underwent a name change in 1910. Today Murdock is a quiet community of about 375 residents.
Austin Smith, “Murdock, Kingman County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/146.
Keywords: Kansas; Kingman County; Lost Towns; Marsh Murdock; Murdock; New Murdock